Coleman Hill : a novel - Foote, Kim Coleman (SJP LIT, a Zando Imprint, 2023)
"In 1916, during the early days of the Great Migration, Celia Coleman and Lucy Grimes flee the racism and poverty of their homes in the post-Civil War South for the "Promised Land" of Vauxhall, New Jersey. But the North possesses its own challenges and bigotries that will shape the fates of the women and their families over the next seventy years. Told through the voices of nine family members--their perspectives at once harmonious and contradictory--Coleman Hill is a penetrating multigenerational debut. Within ten years of arriving in Vauxhall, both Celia and Lucy's husbands are dead, and they turn to one another for support in raising their children far from home. Lucy's gentleness sets Celia at ease, and Celia lends Lucy her fire when her friend wants to cower. Encouraged by their mothers' friendship, their children's lives become enmeshed as well. As the children grow into adolescence, two are caught in an impulsive act of impropriety, and Celia and Lucy find themselves at irreconcilable odds over who's to blame. The ensuing fallout has dire consequences that reverberate through the next two generations of their families. "--Amazon.